KEEFEKTIFAN ORGANISASI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN SUMBA BARAT, PROVINSI NUSA TENGGARA TIMUR - Daniel Umbu Sunga; M. Irwan Tahir; Irawan (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This research aimed to analyze and evaluate the organizational effectiveness of Community and Village Empowerment office in West Sumba District, NTT Province. It involved 43 informants (17 from the PMD office, 2 from the inspectorate, 2 from Bappeda, 3 from the organization, 4 from the sub-district, 13 from the village, 1 from the District PKK, and 1 from the P3MD Professional Companion Staff). Data were collected using qualitative methods (qualitative interviews and qualitative document collection), with a case study research strategy. The collected data were analyzed using an interactive model. The implementation of the duties and functions of the PMD Office of West Sumba District, NTT Province has not been effective, of the 5 effectiveness criteria analyzed and evaluated, it was found that 4 criteria (production, satisfaction, adaptability and development) were still low, and 1 other criteria, namely efficiency was quite high, but did not have a positive correlation with the achievement of its performance.